Enhancing Managerial Efficiency Through a Digital Fingerprint Attendance and Monitoring Dashboard: A Community Empowerment Initiative in the TEFA Integrated Agriculture Unit - Putri Anggraeni, Rosaliana; Mukhsin, Mukhsin (CV. SPDFHarmony, 2025)
Background: Digital transformation in community-based vocational units remains uneven, particularly in agricultural practice settings where daily operations depend heavily on manual labor. Inefficiencies in attendance monitoring and the absence of real-time managerial data often hinder decision-making and limit empowerment opportunities for casual workers. These challenges motivated the implementation of a digital fingerprint attendance system supported by an integrated monitoring dashboard in the TEFA Integrated Agriculture Unit. Aims: The study aims to evaluate how the introduction of a digital attendance and monitoring system influences managerial efficiency while strengthening the foundation for community empowerment among daily workers engaged in agricultural activities. Methods: A mixed-method approach was adopted, integrating observational data, pre- and post-implementation attendance records, and structured interviews with supervisors and casual workers. Quantitative data captured punctuality trends, consistency of attendance, and time-based operational efficiency, while qualitative insights were used to interpret changes in worker engagement and perceptions of digital tools. Results: Findings indicate a substantial improvement in attendance accuracy, reduced reporting delays, and enhanced managerial oversight through real-time dashboard visualization. Supervisors reported greater clarity in workforce allocation, while workers experienced increased transparency regarding working hours. Although empowerment outcomes were not uniform across individuals, most participants acknowledged that the system encouraged discipline and fairness in workload recognition. Conclusion: The introduction of a digital fingerprint attendance system demonstrates meaningful progress toward strengthening managerial efficiency in community-based vocational units. More importantly, the intervention provides an early but significant foundation for community empowerment by fostering transparency, reinforcing equitable work practices, and promoting technological readiness among casual workers. The study suggests that digital tools, when integrated with ongoing capacity-building efforts, can evolve into broader empowerment mechanisms that improve not only administrative efficiency but also workers’ sense of participation, agency, and long-term inclusion in agricultural digitalization initiatives. Future replication in similar rural contexts is promising, provided that training, responsiveness to local needs, and sustained community engagement remain central.